Komunikasi Efektif: Strategi Mewujudkan Keluarga Harmonis Di Desa Paranbatu - Syafaruddin; Muhammad Amsal Nasution; Khoirun Nisa Zein Lubis; Mhd Candra Ali Soti Dlt; Sariyat Hasibuan; Indah Pita Sari Hasibuan (Yayasan Salam Cerdas Al-Fattah, 2025)
The family plays a crucial role in shaping relationships among its members. This study aims to describe the process and outcomes of a socialization program on Islamic communication in Paranbatu Village as an effort to strengthen family resilience through the Kampung Keluarga Berkualitas (Quality Family Village) program. The research employed a descriptive-participatory qualitative method involving 30 participating families, including parents, adolescents, and village cadres. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate an increase in participants’ understanding of open, empathetic, and respectful communication among family members. The socialization activities were conducted through programs involving micro-modules, role-play, family huddles, and family digital literacy. The results suggest that families are expected to develop communication skills and strengthen household harmony. This program is considered replicable and has the potential to be implemented in other villages to support the realization of quality, harmonious, and empowered families within the framework of national development.